ANALISIS PENGARUH KARAKTERISTIK INDIVIDU DAN KARAKTERISTIK PEKERJAAN TERHADAP KEPUASAN KERJA SERTA DAMPAKNYA PADA KOMITMEN ORGANISASI - Ayu Anora; Marbawi Marbawi; Mariyudi Mariyudi (J-MIND (Jurnal Manajemen Indonesia), 2020)
The purpose of this study is to examine the analysis of the effect of individual characteristics and job characteristics on job satisfaction and its impact on organizational commitment. This study uses individual characteristics and job characteristics as independent variables, this study also uses job satisfaction as intervening variable and organizational commitment as a dependent variable. The study was conducted at the Office of Independent Election Commission of Lhokseumawe City. In this study used simple random sampling technique that is by giving questionnaires to the sample respondents. This sample amounted to 125 respondents. Data analysis techniques in this study using SEM (Structural Equation Modeling) analysis which is operated through WarpPLS 3.0 program. The results of this study indicate that individual characteristics and job characteristics have a significant effect on job satisfaction and increase organizational commitment. On the other hand the effect of job satisfaction on organizational commitment is significant. Job satisfaction mediates the relationship between individual characteristics and job characteristics to organizational commitment is positively significant.  Keywords: Individual Characteristics, Job Characteristics, Job Satisfaction, Organizational Commitment